Partisipasi Masyarakat Lokal Terhadap Wisata Edukasi Di Green School Bali, Abiansemal, Badung - Muslimin, Andra; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA; Vol 6 No 1 (2018): VOL 6, NO 1 (2018): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i01.p01, 2018)
This study was conducted with the aim of identifying the form of local community participation in educational tourism implemented by Green School Bali, Abiansemal, Badung. The data collection methods that used were observation, in-depth interview, literature study and documentation. The data analysis techniques that used are qualitative data analysis. The form of local community participation in the implementation of Green School Bali educational tour is categorized in vertical participation because the role of local communities in this educational tour is located as a subordinate or worker status. This happens because the tour that held in Green School Bali is a non profit-based, the income obtained by the tour will be fully allocated to the scholarship students in Green School Bali. Keywords: Community Based Tourism, Educational Tourism